2016
DOI: 10.1037/xap0000104
|View full text |Cite
|
Sign up to set email alerts
|

Interword and interletter spacing effects during reading revisited: Interactions with word and font characteristics.

Abstract: Despite the large number of eye movement studies conducted over the past 30+ years, relatively few have examined the influence that font characteristics have on reading. However, there has been renewed interest in 1 particular font characteristic, letter spacing, which has both theoretical (visual word recognition) and applied (font design) importance. Recently published results that letter spacing has a bigger impact on the reading performance of dyslexic children have perhaps garnered the most attention (Zor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 65 publications
4
22
0
Order By: Relevance
“…In summary, in line with previous eye-tracking experiments on paragraph reading in English (Slattery et al, 2016) and Spanish (Perea et al, 2016) we observed in a sample of young German readers without a history of reading impairments that wider character spacing produced robust effects of shorter fixation durations that did, however, not translate into reading rate gains. On the contrary, reading rates were slowed down, an effect that was stronger for faster readers and appears attributable to increased numbers of fixations under conditions of wider letter spacing.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In summary, in line with previous eye-tracking experiments on paragraph reading in English (Slattery et al, 2016) and Spanish (Perea et al, 2016) we observed in a sample of young German readers without a history of reading impairments that wider character spacing produced robust effects of shorter fixation durations that did, however, not translate into reading rate gains. On the contrary, reading rates were slowed down, an effect that was stronger for faster readers and appears attributable to increased numbers of fixations under conditions of wider letter spacing.…”
Section: Resultssupporting
confidence: 91%
“…Also, the shorter duration of fixations quite obviously reflects that less information can enter through foveal vision if letters are expanded over a larger part of the visual field in the wider letter spacing condition. This, as a consequence, also generated the need for additional fixations, leading to the observed effect of slower reading rates despite shorter fixation durations, which replicates previous reports for non-impaired readers of Spanish (Perea and Gomez, 2012b;Perea et al, 2016), Hungarian (Weiss et al, 2016), and English (Slattery et al, 2016;Li et al, 2019). An important novel result of the current study is that the strength of the letter spacing effect is mediated by inter-individual differences in reading proficiency: whereas faster readers can suffer substantially from wider letter spacing (i.e., up to 20 to 30 words per minute), slower readers show no or comparably weak effects ( Figure 4B).…”
Section: Overall Reading Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…Many other fonts used by word processers today utilize proportional fonts (i.e., the computer adjusts for the unique width of each character). Slattery, Yates, and Angele (2016) recently found that interword spacing effects differed depending on whether a fixed width font on a proportional width font was used. Thus, it is possible that the effects of punctuation spacing seen in the current experiment may differ when presented in other font conditions (or other writing systems).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Verdana showed comparatively little change with letter spacing. The effects of interword and interletter spacing on reading are known to interact with font characteristics [12].…”
Section: Font Compression and Expansionmentioning
confidence: 99%